Current Issues of Intermedial Scholarship Discussed with Editors of Book Series and Journals Specializing on Intermediality - Ágnes Pethő (Acta Universitatis Sapientiae: Film and Media Studies)
The conference entitled Affective Intermediality, organized between 20–21 October 2023 at the Sapientia Hungarian University of Transylvania in Cluj-Napoca, included a hybrid (i.e. online and in person) round table presentation of book series and peer reviewed journals specializing or frequently publishing on intermediality (as the 2nd Meeting of Researchers in Intermediality initiated by Ana Munari). As a followup to this round table, a more detailed discussion was initiated with editors (who are also researchers themselves) about the state of the art in intermediality studies, the main challenges in the field, the diversity of topics and approaches, and the possible new directions including the one proposed by the organizing research team focusing on the idea of “affective intermediality.” The participants in this discussion were asked by Ágnes Pethő to answer five groups of questions with the aim of providing an inspection of key issues affecting the study of intermediality, and to offer an overview of ideas that have emerged from the diversification of intermedial scholarship practiced in various parts of the world. Although far from comprehensive in its covering of geographical areas or publication outlets, with some of the answers more succinct than the others, this survey puts a spotlight on important publications and theoretical concerns of intermedial scholarship today. It probably raises even more questions that might be the focus of further debates.